Pembubaran Organisasi Kemasyarakatan Hizbut Tahrir Indonesia Perspektif Fiqh Siyasah Dusturiyah - Nizam Ubaidillah; Nurul Syalafiyah (Universitas Pangeran Diponegoro Nganjuk, 2025)
The dissolution of the mass organization Hizbut Tahrir Indonesia (HTI) by the Indonesian government in 2017 has generated significant discourse concerning its legal foundations and implications from the perspective of Fiqh Siyasah Dusturiyah (Islamic Constitutional Jurisprudence). This decision was enacted through Government Regulation in Lieu of Law (Perppu) Number 2 of 2017, which amended Law Number 17 of 2013 on Community Organizations. The government justified this action by asserting that HTI's activities were incompatible with the principles of Pancasila and the 1945 Constitution, and posed a potential threat to the unity and integrity of the Unitary State of the Republic of Indonesia (NKRI). From the lens of Fiqh Siyasah Dusturiyah, this measure can be interpreted as an initiative to safeguard public welfare (maslahah) and prevent harm (dar’u al-mafasid), aligning with Islamic political principles that emphasize the importance of national stability and security. Nevertheless, the dissolution has also ignited debates surrounding the protection of fundamental rights, particularly freedom of association and expression, within the framework of a democratic state governed by the rule of law. This tension highlights the complex interplay between state authority, constitutional principles, and the protection of civil liberties in a pluralistic society.